Hanseniasis in the municipality of Western Amazon (Acre, Brazil): are we far from the goal of the World Health Organization? - Araújo,Francisco A. (2021)
ABSTRACT Background: Hanseniasis is a public health concern in developing countries. Although a decrease in the number of new cases in Brazil has been reported, there is a prevalence above that recommended in some regions. Aims: Considering the goal of the World Health Organization (WHO) to accelerate towards a leprosy-free world from 2020, the aim of this study was to analyze the epidemiological profile and leprosy trends in the city of Cruzeiro do Sul, Acre, Brazil. Methods: This retrospective cohort study analyzed the epidemiology and trends of hanseniasis between 2005 and 2018, monitoring socioeconomic and clinical epidemiological variables obtained from the Information System of Notifiable Diseases of Hanseniasis (SINAN) database. Results: A total of 422 cases of hanseniasis (284 male, 138 female) were included. The questionnaire of six patients was incomplete. The highest number of cases (89) was recorded in 2006 (11.7/10,000 inhabitants). The borderline clinical form was most common, with 45.4% of cases. Throughout the historical series, the rate of annual percentage change in the detection of new cases and cases with grade 2 disability showed a decreasing profile, at −13.9 [95% CI: −19.1, −8.2] and −13.1 [95% CI: −21.8, −5.5], respectively. The same rates were observed in patients below 15 years of age. Limitations: This study reflects the scenario in one reference center and data were obtained retrospectively. Conclusions: The incidence of hanseniasis in this reference center is declining gradually; however, the indicators show active disease transmission and late diagnosis.